Kinerja Keuangan dan Belanja Kota Pasuruan Tahun 2019-2023 - Adinda Yasinta Nurul Hasan; Aqilla Nabbihah; Berlian Gustina Riyadi; Ferdiaz Riandra Febrilliant; Renita Syilviana; Mega Tunjung Hapsari (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The aim of this research will focus on the management of Regional Original Income and regional expenditure in Pasuruan City. Descriptive qualitative analysis methods will be used to explain the research results. Data obtained from the realization of Pasuruan City's financial reports for 2019-2023. The results of the analysis show that the degree of decentralization ratio has poor performance. The average performance financial independence ratio is very low. The average performance of the expenditure growth ratio is not good. Average operational expenditure performance is good. Average capital expenditure performance is good.